Fludarabine modulates expression of type VII collagen during haematopoietic stem cell transplantation for recessive dystrophic epidermolysis bullosa. (1st August 2021) - Vanden Oever, M.; Muldoon, D.; Mathews, W.; Tolar, J.
Summary: Background: Recessive dystrophic epidermolysis bullosa (RDEB) is a severe, complicated inherited blistering skin disease with few treatment options currently available. Recently, haematopoietic stem cell transplantation (HCT) has been used as an alternative therapy that can improve skin integrity, but it is not known if the preparative HCT regimen also contributes to the therapeutic response. Objectives: To determine whether chemotherapy drugs used in the HCT preparative regimen influence type VII collagen (C7) expression, which is inherently reduced or absent in RDEB skin, and to explore the pathomechanisms of such responses, if present. Methods: Drugs from the HCT preparative regimen (busulfan, cyclophosphamide, ciclosporin A, fludarabine and mycophenolate) with inhibitors (PD98059, U0126, LY294002, SR11302, SIS3 and N ‐acetyl‐l ‐cysteine) were added to normal human dermal and human RDEB fibroblasts. C7 expression was measured using reversetranscription polymerase chain reaction and immunoblotting. Results: We uncovered a previously unknown consequence of fludarabine whereby dermal fibroblasts exposed to fludarabine upregulate C7. This effect is mediated, in part, through activation of the mitogen‐activated protein kinase/extracellular signal‐regulated kinase, phosphoinositide 3‐kinase/protein kinase B and transforming growth factor‐β pathways. Activation of these pathways leads to activation of downstream transcription factors, including activator protein 1 (AP‐1) and SMAD. Subsequently, both AP‐1 and SMAD bind the COL7A1 promoter and increase COL7A1 expression. Conclusions: Fludarabine influences the production of type VII collagen in RDEB fibroblasts.